Analisis Hukum Islam Terhadap Cryptocurrency Sebagai Alat Tukar Dan Relevansinya Dengan Konsep Evolusi Uang Al-Ghazali - Nurziah, Evi; Fikriawan, Suad; Fathoni, Khoirul (Social Science Academic, 2023)
In everyday life, humans always carry out economic activities, one of which is the activity of transacting with money. Dinars and dirhams in Islam are likened to money in the present. Both of these objects are metals that originally did not have any use value. Imam al-Ghazali describes his opinion regarding the function and concept of money in his book. Then, in line with the times, money began to evolve from bartering to digital money. This research study was conducted to gain insight related to the analysis of al-Ghazali's financial concepts and functions and their relevance to cryptocurrency money when used as a medium of exchange. This research is included in library research, namely research with the aim of obtaining information and knowledge about various materials contained in the library, such as books, theses, theses, journals and other scientific works that are still related to the subject matter. The conclusion from the results of this study is that al-Ghazali's financial concept is not in accordance with the cryptocurrency financial concept, because al-Ghazali is of the opinion that money used as a medium of exchange must come from a state or government agency starting from printing to determining the value of the amount of money. Furthermore, cryptocurrency itself can be used as a medium of exchange, because cryptocurrency is adopted as a currency that has generally passed Ta'amul, which means that these assets can only be used as a medium of exchange after the masses/public start using them and acknowledging them. Kata Kunci: Al-Ghazali, Cryptocurrency, Money